Acceptability and feasibility of the Home Support Needs Assessment in a forensic mental health service: An initial study - Aleksandra Westcott; Lorrae Mynard; Gabrielle Pitt; Susan Darzins (Australian Occupational Therapy Journal, 2026)
Abstract Introduction Identifying and addressing the support needs of forensic mental health patients in daily life occupations is critical yet complex due to the health comorbidities and environmental restrictions impacting their participation. Occupational therapists support forensic patient recovery by facilitating their performance in daily life occupations required at home and in the community. Standardised assessments of daily living are important for guiding interventions. The Home Support Needs Assessment (HSNA) is a standardised measure identifying unmet support needs in daily life occupations. The aim of this study was to evaluate its initial acceptability and feasibility for occupational therapists' use in a forensic mental health setting. Methods An exploratory convergent, parallel mixed‐methods design was used. Semi‐structured interviews with five forensic occupational therapists explored their perspectives about using the HSNA in practice. Interview transcripts were analysed using reflexive thematic analysis. HSNA data were extracted from 13 patient medical records and summarised using descriptive statistics. Consumer and Community Involvement There was no consumer and community involvement in this research as the focus of the study was on occupational therapists. Findings Three overarching themes were generated: value of the assessment , informed care planning , and applicability to the environment . The HSNA was found to structure observations, facilitate discussions about daily life occupations, and clarify ongoing support needs. An over‐support of some needs emerged as a unique factor of the forensic mental health environment. Some items were viewed as not applicable to the setting. Conclusion The HSNA highlighted that the safety focus of the secure environment inadvertently limited opportunities for patients' involvement in daily life occupations. Acceptability was associated with enabling holistic occupational assessment. Further tailored training may increase overall implementability.